The nation under neoliberalism: Spain’s Nation Brand as an ideological arm of the government - Boyco Orams, Alejandro (2020)
Nation branding has been studied in academia as a phenomenon where national identity construction and the external image of each country responds to neoliberal techniques. Following the need to exploit comparative advantages of each country, different specialists linked with publicity and marketing emerge and become experts in converting national identity into an exportable brand, assuring success in international rankings. The case of Spain’s nation brand proves how the government maintains an active influence in the publicity campaign and in the neoliberal construction of the national identity. A discursive analysis of the audio-visual campaign in the official YouTube channel of Spain’s nation brand proves that the message transmitted responds to the objectives and ideology of the ruling government and changes with time, while different political processes redefine the ends of the government’s policy. These processes include overcoming the economic crisis, positioning Spain in the international arena, Spain’s influence in the UN’s Security Council, and maintainingunity against the threat of independent movements in Cataluña. The low autonomy of the administrative institution in charge of Spain’s nation brand from the ruling party explains the high influence the government has in the publicity campaign. Spain’s nation brand is not a neutral process: it is used as one of the government’s political and ideological arms to reach its goals.